TCR Signaling Emerges from the Sum of Many Parts - Kuhns, Michael S.; Davis, Mark M. (Frontiers in Immunology, 2012)
“How does T cell receptor signaling begin?” Answering this question requires an understanding of how the parts of the molecular machinery that mediates this process fit and work together. Ultimately this molecular architecture must (i) trigger the relay of information from the TCR-pMHC interface to the signaling substrates of the CD3 molecules and (ii) bring the kinases that modify these substrates in close proximity to interact, initiate, and sustain signaling. In this contribution we will discuss advances of the last decade that have increased our understanding of the complex machinery and interactions that underlie this type of signaling.